Tingkat Kesejahteraan Petani Jagung di Desa Rasau Jaya Satu Kecamatan Rasau Jaya Kabupaten Kubu Raya - maya tiara anggreini; adi suyatno; anita suharyani (Jurnal Sains Pertanian Equator, 2021)
ABSTRACTWelfare is the fulfillment of the condition of the material, spiritual and citizens in order to live a decent and able to develop themselves, so that it can carry out their social functions.The aim of this study to analyze the level of welfare of corn in the village of Rasau Jaya Satu, Rasau Jaya District, Kubu Raya Regency. The method used is a survey method, while samples were taken randomly. The sample was 41 respondents of 629 corn farmer populations. Farmers collecting data through interviews using a questionnaire. The variables in this study is the corn farmer incomes derived from on farm incomes, off-farm income and non-farm income household consumption of food and non-food consumption. The welfare level analysis is calculated based on the percentage of food consumption expenditure (Gilarso). Results of the analysis of the income and welfare corn farmer in the village of Rasau Jaya Satu, Rasau Jaya  District, Kubu Raya Regency, the average income was Rp.627.872 / month, the level of welfare based on corn farmer the analysis of food consumption expenditures for included in the low welfare level category of 60-100% for corn farmer on farm,included in the category of moderate welfare level of 40-75% for corn farmer on farm, and included in the category of moderate welfare level of 40-75% for corn farmer non farm.Keyword: Income, Welfare, Corn Farmer ABSTRAKKesejahteraan adalah kondisi terpenuhinya kebutuhan material, spiritual dan sosial warga negara agar dapat hidup layak dan mampu mengembangkan kan diri, sehingga dapat melaksanakan fungsi sosialnya. Penelitian ini bertujuan untuk menganalisis tingkat kesejahteraan petani jagung di Desa Rasau Jaya Satu Kecamatan Rasau Jaya Kabupaten Kubu Raya. Metode yang digunakan adalah metode survey, sedangkan sampel penelitian ini diambil secara acak sederhana (simple random sampling). Sampel dalam penelitian sebanyak 41 responden dari 629 populasi petani jagung. Teknik pengumpulan data melalui wawancara menggunakan kuesioner. Variabel dalam penelitian ini adalah pendapatan petani jagung yang berasal dari pendapatan on farm, pendapatan off farm dan pendapatan non Farm serta konsumsi rumah tangga dari konsumsi pangan dan konsumsi non pangan. Analisis tingkat kesejahteraan dihitung berdasarkan presentasi pengeluaran konsumsi pangan (Gilarso). Hasil analisis pendapatan dan kesejahteraan petani kelapa sawit di Desa Sape Kecamatan Jangkang Kabupaten Sanggau rata-rata pendapatan sebesar Rp. 627.872,43/bulan, tingkat kesejahteraan berdasarkan analisis pengeluaran konsumsi pangan petani jagung masuk dalam katagori tingkat kesejahteraan rendah sebesar 66-100% petani jagung on farm, masuk dalam kategori tingkat kesejahteraan rendah sebesar 40-75% petani jagung on farm dan masuk dalam katagori tingkat kesejahteraannya sedang  40-75% petani jagung off farm.Kata kunci: Pendapatan, Tingkat kesejahteraan, Petani Jagung